(untitled) (REMUNOM, 2025)
The advancement of digital media and the growth of social media have fueled the emergence of new professions, such as digital influencers and content creators. However, many of these professionals still operate without proper accounting and tax knowledge, which can compromise the legality and sustainability of their activities. The overall objective of this study is to analyze how accounting and tax analysis can assist in the regularization and management of the activities of digital influencers and content creators. The research is qualitative and exploratory in nature, with a bibliographical approach. Current legislation, scientific articles, specialized works, and technical materials focused on accounting applied to the digital market were analyzed. The results indicate that formalizing as a legal entity is an advantageous alternative, allowing adaptation to the most appropriate tax regime, such as Simples Nacional for beginner influencers or those with lower revenue, Presumed Profit for influencers with high margins and few expenses, or Real Profit for large influencers with large teams and costs. Choosing the right regime will help reduce the tax burden. The study therefore highlights the importance of understanding the importance of fiscal and tax accounting for financial and strategic planning, and how formalizing the activity as a legal entity can contribute to adherence to a tax regime appropriate for this type of activity.